PENGEMBANGAN MEDIA PEMBELAJARAN MORAYA (MONOPOLI KEBERAGAMAN BUDAYA) KELAS IV DI SDN 5 KWANDANG, GORONTALO - Abdullah, Ewintha Ayudia; Pomalingo, Samsi; Nurainun, Nurainun (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study develops Moraya learning media (Cultural Diversity Monopoly) for fourth-grade students at SDN 5 Kwandang, Gorontalo. The background of this research is the difficulties students face in understanding cultural diversity material due to the minimal use of concrete-based media. Using the ADDIE development model, this research includes five stages: analysis, design, development, implementation, and evaluation. The Moraya media is designed to combine elements of the classic Monopoly game with interactive learning material, allowing students to explore and understand various aspects of Indonesian culture. The validation results indicate that this media is very feasible to use, with an average score of 99.30%. A limited trial on 14 students showed a significant improvement in student understanding, with the average pre-test score rising from 32.85% to 85.71% on the post-test, and an N-Gain Score of 0.78 indicating the medium's effectiveness. Observations during implementation showed that students were very enthusiastic and able to collaborate, creating a fun and interactive learning atmosphere. The Moraya media not only enhances students' understanding of cultural diversity but also instills values of tolerance and mutual respect. Thus, it can be concluded that Moraya media is effective in supporting